2021
DOI: 10.1186/s13018-020-02197-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of percutaneous cross screw fixation versus open reduction and internal fixation for pelvic Day type II crescent fracture-dislocation: case-control study

Abstract: Objective To investigate the clinical outcomes of percutaneous cross screws internal fixation for pelvic Day type II crescent fracture-dislocation. Methods We reviewed 66 consecutive patients undergoing surgical treatment for Day type II crescent fracture-dislocation from June 2005 to December 2017. Percutaneous cross screws internal fixation was performed in 40 patients, and open reduction and internal fixation was performed in 26 patients. The pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It is believed that the dislocation of crescent fractures primarily destroys rotational stability, but the stability in the vertical direction is barely affected 4,5 . However, recent research revealed that stability in the vertical direction may also be affected in crescent fractures, suggesting that the current understanding of crescent fracture dislocation is incomplete 17,18 . In our clinical work, we found five cases of this type of injury in the Day types 2 and 3 groups.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It is believed that the dislocation of crescent fractures primarily destroys rotational stability, but the stability in the vertical direction is barely affected 4,5 . However, recent research revealed that stability in the vertical direction may also be affected in crescent fractures, suggesting that the current understanding of crescent fracture dislocation is incomplete 17,18 . In our clinical work, we found five cases of this type of injury in the Day types 2 and 3 groups.…”
Section: Discussionmentioning
confidence: 59%
“…4,5 However, recent research revealed that stability in the vertical direction may also be affected in crescent fractures, suggesting that the current understanding of crescent fracture dislocation is incomplete. 17,18 In our clinical work, we found five cases of this type of injury in the Day types 2 and 3 groups. In these groups, the vertical displacement was >10 mm, and the posterior ring was completely unstable during the examination under anesthesia (EUA).…”
Section: Shortcomings Of Past Researchmentioning
confidence: 70%
“…Starr [11] proposed a minimally invasive technique using cannulated LC-II screws to treat pelvic crescent fractures, which preserves the blood supply to the bone, reduces the incidence of a soft tissue injury, and decreases intraoperative blood loss. With the increasing popularity of minimally invasive techniques and the use of navigation devices such as the TiRobot [12,13], percutaneous cross-screw xation techniques have been widely applied in the clinical management of CFDP [14].…”
Section: Introductionmentioning
confidence: 99%